PEMBERDAYAAN MADRASAH DINIYAH:BELAJAR PADA SEABAD MADIN MUAWANATUL MUSLIMIN DI KUDUS - Rosyid, Moh. (Pascasarjana IAIN Kudus, 2014)
In 1915 ulama of Kudus founded the Madin Muawanatul Muslimin (MDMM) originally this Madin studied the Quran in mosque of Abyadl. This research is aimed to know about the history of the MDMM, What constraint is it faced, and how is the empowerment of its management. Research goals are to understand the history of MDMM, its constraint, and shape of empowerment. Benefits of research are as a contribution to Madin’s management when dealing with constraints, to learn from the uniqueness MDMM and to enrich research about Madin. The data is taken from end of 2012 until mid of 2013. Informants are managements and foundation staff of Madin. Objects of research: students, teachers and administration staff in random. Data is collected through observation, interviews, documentation, and triangulation. Data analysis is descriptive qualitative. The uniqueness of MDMM: its subjects, only male students, affordable cost, holiday, and evaluation. The obstacles are: no graduate certificate, minimum sources of funds; increasing number of TPQ, minimum learning tools, extracurricular and additional hours of formal education. Similarities with other Madin are teachers and students wear sarong, peci, slippers, ad few wear trousers but forbid to wear t-shirt. Learning hours start from 2 p.m. to 5 p.m., in which from 7 a.m. to 1 am students go to formal education. Strength lies on charisma of the teachers; uniqueness of learning subjects; afternoon learning hours; affordable cost; parents and students expect teachers blessing; expect success as graduates MDMM, and teachers struggle in the name of religion. In 2013, MDMM reaches anticlimactic, with no student in first level of Wustho .